On a collection of Dromiidae and Dynomenidae from the Philippines, with description of a new species of Hirsutodynomene McLay, 1999 (Crustacea: Decapoda: Brachyura) - Mclay, Colin L.; Ng, Peter K.l. (Zootaxa, 2005)
A total of 24 dromiid and six dynomenid crab species are now known from the Philippines. Newly recorded dromiids for the islands are Lauridromia dehaani (Rathbun, 1923), Cryptodromia coronata Stimpson, 1858, Cryptodromia pileifera Alcock, 1901, Epigodromia areolata (Ihle, 1913), and Takedromia longispina McLay, 1993; the new dynomenid records being Acanthodromia margarita (Alcock, 1899), Hirsutodynomene vespertilio n. sp. and Metadynomene tanensis (Yokoya, 1933). A revised key to the species of Hirsutodynomene is provided.